Promising metal-thermal technologies for titanium production - Ignatiev , V.S.; Holovachov , A.M.; Kolbin , M.O.; Yaroshenko , Ya.O.; Ovcharuk , A.M. (Theory and Practice of Metallurgy, 2025)
This review discusses existing and new titanium production technologies, their advantages and disadvantages. The current global production of titanium metal is based on the production of titanium sponge by reducing titanium tetrachloride with liquid magnesium and then purifying it by electric arc remelting (Kroll’s metallothermal method). The Kroll method has some disadvantages: periodicity of the process, low speed, and high cost of raw materials. The paper analyzes a number of fundamentally new technological schemes for titanium production: magnetism in salt melts; magnetism in a liquefied layer of magnesium particles (TIRO process); sodium jet thermionic (Armstrong process); steam process. In the near future, we can expect a breakthrough in titanium technology that will reduce its cost.